Novel levan and pNIPA temperature sensitive hydrogels for 5-ASA controlled release - TOKSOY ÖNER, EBRU; EROĞLU, MEHMET SAYIP (ELSEVIER SCI LTD, 2017)
Levan based cross-linker was successfully synthesized and used to prepare a series of more biocompatible and temperature responsive levan/N-isopropyl acrylamide (levan/pNIPA) hydrogels by redox polymerization at room temperature. Volume phase transition temperature (VPTT) of the hydrogels were precisely determined by derivative differential scanning calorimetry (DDSC). Incorporation of levan into the pNIPA hydrogel increased the VPTT from 32.8 degrees C to 35.09 degrees C, approaching to body temperature. Swelling behavior and 5-aminosalicylic acid (5-ASA) release of the hydrogels were found to vary significantly with temperature and composition. Moreover, a remarkable increase in thermal stability of levan within hydrogel with increase of pNIPA content was recorded. The biocompatibility of the hydrogels were tested against mouse fibroblast L929 cell line in phosphate buffer saline (PBS, pH 7.4). The hydrogels showed increasing biocompatibility with increasing Levan ratio, indicating levan enhanced the hydrogel surface during swelling. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Levan; N-Isopropyl acrylamide; 5-ASA; Temperature sensitive hydrogel; Controlled drug release; Redox polymerization; N-ISOPROPYLACRYLAMIDE; HALOMONAS-SMYRNENSIS; DRUG-RELEASE; DEGRADATION; DELIVERY; DEXTRAN; FILMS; CELLULOSE; POLYMERS